A diagnostic challenge of tongue botryomycosis miming mycetoma-A case report - Emmanuel Edwar Siddig; Ayman Ahmed (Wiley, 2024)
Abstract Botryomycosis of the tongue is a rare chronic bacterial infection that presents as nodular masses, mimicking other infectious or neoplastic conditions such as mycetoma. A case of an 80‐year‐old male was presented with painless swelling on the right lateral side of his tongue to the outpatient clinic. Biopsy and microbiological investigations revealed an unexpected Staphylococcus aureus‐related botryomycosis. This case highlights the diagnostic challenge for unusual clinical presentations of bacterial infections. Healthcare providers in countries endemic with diseases that manifest similarly should investigate thoroughly to ensure a positive clinical outcome through early diagnosis and effective case management.